Pengaruh Konsentrasi Xilosa dan Kosubstrat Terhadap Produksi Xilitol oleh Candida shehatae Way 08 - Wisnu Adi Yulianto; Kapti Rahayu Kuswanto; Tranggono Tranggono; Retno Indrati (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2005)
The objectives of the research were to determine the optimum cultivation condition of initial xylose concentration, type of cosubstrate and ratio of cosubstrate to substrate (xylose) for xylitol production by Candida shehatae WAY 08. The initial xylose concentrations were varied within the range of 2-14 %. The cosubstrates were arabinose, galactose, glucose, and mannose. Ratios of cosubstrate to xylose were the range of 1:6 - 3:6 %. The fermentation was performed at 30`C in a 500 ml Erlenmeyer flask placed in a shaker incubator at 200 rpm for 72 h. Biomass concentration was determined by drying method. Xylose, cosubstrate and xylitol concentrations were determined using HPLC. The result indicated that with the medium containing 6 % xylose produced the highest product yield ( 0,75 g/g) and xylitol volumetric productivity was 0,73 g/Lh. The addition of cosubstrate of arabinose increased xylitol production, while the addition of glucose, galactose, and mannose decreased its productions.